High stress actuation by dielectric elastomer with oil capsules - La, Thanh-Giang (2014)
Though capable of generating a large strain, dielectric elastomer actuators (DEAs) generate only a moderate actuation stress not more than 200kPa, which seriously limits its use as artificial muscles for robotic arm. Enhancement of dielectric strength (greater than 500MV/m) by dielectric oil immersion could possibly enable it a larger force generation. Previously, the immersion was done in an oil bath, which limits portability together with DEAs. In this study, we developed portable capsules to enclose oil over the DEA substrate (VHB 4905). The capsules is made of a thinner soft acrylic membrane and they seals dielectric liquid oil (Dow Corning Fluid 200 50cSt). The DEA substrate is a graphiteclad VHB membrane, which is pre-stretched with pure-shear boundary condition for axial actuation. When activated under isotonic condition, the oil-capsule DEA can sustain a very high dielectric field up to 903 MV/m and does not fail; whereas, the dry DEA breaks down at a lower electric field at 570 MV/m. Furthermore, the oil-capsule DEA can produces higher isometric stress change up to 1.05MPa, which is 70% more than the maximum produced by the dry DEA. This study confirmed that oil capping helps DEA achieve very high dielectric strength and generate more stress change for work.